2011
DOI: 10.2118/128047-pa
|View full text |Cite
|
Sign up to set email alerts
|

Propagation and Retention of Viscoelastic Surfactants Following Matrix-Acidizing Treatments in Carbonate Cores

Abstract: Viscoelastic surfactants have been used extensively in the field. They have the ability to form long rod-like micelles with an increase in pH and calcium concentration, which results in increasing the viscosity and elasticity of partially spent acids. There is ongoing debate in the industry about whether the gel generated by these surfactants causes formation damage, especially in dry-gas wells. The objectives of the present study are to quantitatively determine surfactant retention in calcite cores and assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…This will help the acid plug the high-permeability zones upon acid spending and divert the fresh acid to the low-permeability zones. Yu et al (2012) studied the effect of hydrolysis on the rheology of VES-based acid systems. Under high temperature and in an acidic environment, the peptide bond is broken and the system is hydrolyzed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This will help the acid plug the high-permeability zones upon acid spending and divert the fresh acid to the low-permeability zones. Yu et al (2012) studied the effect of hydrolysis on the rheology of VES-based acid systems. Under high temperature and in an acidic environment, the peptide bond is broken and the system is hydrolyzed.…”
Section: Discussionmentioning
confidence: 99%
“…This resulted in a large decrease in the acid viscosity. Yu et al (2012) shows the VES-based acid-phase separation as a function of hydrolysis time at 190 F for 4-, 6-, and 8-vol% VES concentration (Figs. 3 through 5).…”
Section: Discussionmentioning
confidence: 99%
“…Upon the reaction of acid with carbonates, the pH increases and the concentration of divalent cations in solution increases and therefore the VES-based acid system starts to build viscosity. At pH around 4, the viscosity of the spent acid will be high enough to divert the fresh acid to low permeability un-contacted zones and fresh acid starts to penetrate and react with these rocks to form wormholes (Nasr-El-Din et al 2006b;Crews and Huang 2007;Huang et al 2008b;Yu et al 2011). The viscosity of VES fluids can be reduced upon mixing with hydrocarbons.…”
Section: B Matrix Acidizingmentioning
confidence: 99%
“…Also, they found that the use of internal breaker is very important to break down the remaining VES structure to better clean up the formation after the acid treatment. Yu et al (2011) studied the retention of VES surfactant in the porous media through using coreflood experiments. The VES-based acid system used in their study consisted of 15 wt% HCl, 7 vol% VES and 0.3 vol% corrosion inhibitor.…”
Section: B1 Experimental Studiesmentioning
confidence: 99%
“…VES result in a rapid viscosity built up due to the entanglement of these rod-like micelles. VES are being used in the petroleum industry for matrix stimulation and enhanced oil recovery (EOR) (Adejare and Nasralla, 2012;Aoudia et al, 2010;Hull et al, 2016;Kamal et al, 2017a;Yu et al, 2011). Matrix stimulation is often needed in limestone and dolomite reservoirs to generate wormholes.…”
Section: Introductionmentioning
confidence: 99%